Object-Oriented Design for Temporal GIS. - Wachowicz, Monica (Research monographs in geographic information systems., 1999)
Explores the major components of the object-orientated analysis and design methods, how they can be used for modelling spatio-temporal data, and how these components are developed and maintained within GIS.